Frequencies determination of characters for Bahasa Melayu: results of preliminary investigation - Shah, Asadullah; Saidin, Aznan Zuhid; Alshaikhli, Imad Fakhri Taha; Zeki, Akram M. (Elsevier, 2011)

(untitled)
Bahasa Melayu (Malay language) is a language spoken in Malaysia and many countries around it. It has rich literature and deep roots in culture. Bahasa Melayu language uses roman character set (i.e. A-Z) identical to English language. The written language uses the character set as building blocks to build word, sentences and phrases along with special punctuations and signs to create documents of interest. In this paper, results of preliminary investigation of Malay text documents are provided. For this purpose scanning of articles written upon various topics in Malay were carried out. Approximately 31 thousand characters from different articles are scanned. Preliminary observations indicate that on average, character “A” occurs 19%, character “N” occur 10%, character “E” occur “9%”and character “I” 8% in text. However, it is also observed from the data that, these are the characters from over all set with highest frequencies of occurrences and it is expected that during further investigation they will remain as higher frequency occurring characters. Furthermore, the results indicate that for Bahasa Melayu characters appearance in text is very close in character frequencies of Bahasa Indonesia, but having different appearance of characters than English language. The investigation also indicate that these two languages, Bahasa Melayu and Bahasa Indonesia share close phonetic structure but not English, though all three use same character set.